The Effect of Self-Efficacy and Work-Life Balance on Employee Engagement and Performance - Nurdzakin, Muhammad; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to explain and analyze the effects of work-life balance and self-efficacy on employee performance with employee engagement as a mediating variable. Design/Methodology/Approach – This study employs a quantitative research approach. Data were collected through questionnaires involving all 134 employees of the Population and Civil Registration Office of Malang City as the research sample using a saturated sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 3.2.9. Findings – The results show that work-life balance and self-efficacy have positive and significant effects on employee performance. Additionally, work-life balance and self-efficacy positively and significantly influence employee engagement, while employee engagement also has a positive and significant effect on employee performance. The findings confirm that employee engagement partially mediates the relationship between work-life balance and self-efficacy on employee performance. Originality/Value This research provides value by empirically demonstrating the mediating role of employee engagement in the relationship between work life balance, self-efficacy, and performance, offering insights that help organizations design more effective human resource strategies.